Innovation and Economic Development: Case of Tunisia - Samet, Kaies; Yahyaoui, Abdelkarim; Saidi, Ahlem; Al Saggaf, Majid Ibrahim (International Journal of Economics and Financial Issues, 2019)
This paper empirically inspects the link between innovation and economic development in Tunisia, both in a direct and indirect contribution of the research and development to the total factor productivity growth and therefore to the economic growth. At this level, we will carry out an empirical inquiry through using an endogenous growth model, covering the period 1970-2008. The results of estimation prove that contrarily to a developed country, Tunisia was not able to benefit from its own R&D capital stock in one part, neither from the R&D conducted in developed countries through international trade and foreign direct investment in another part, which do not seem to be a technology transfer vector in our country. This can be explained essentially by the weakness of the national absorptive capacities, which is itself ought to the inefficiency of the Tunisian educational systems. A significant investment in R&D combined with some brain gain could be adequate solutions for our country in terms of technology. Keywords: R&D, Innovation, productivity, economic development, economic openness, foreign direct investment (FDI), absorptive capacity JEL Classifications: C1, F0, O1, O3, O4 DOI: https://doi.org/10.32479/ijefi.8444